PROMOTING UZBEK NATIONAL CLOTHING MOTIFS AMONG YOUTH THROUGH FASHION EDUCATION - Rajabova Nilufar Shuhratovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines strategies for promoting Uzbek national clothing motifs among youth through fashion education. It explores how traditional patterns, embroidery, and colors can be integrated into educational programs to foster cultural awareness, creativity, and technical skills among students. The study highlights pedagogical approaches, including project-based learning, workshops, and digital tools, to make heritage-based fashion education engaging and effective for young learners.